2009
DOI: 10.1093/eurheartj/ehp211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on both functional and structural measures of premature atherosclerosis

Abstract: The present results demonstrate that bariatric surgery-induced diminution of visceral fat improves both functional and structural markers of early atherosclerosis, providing a link between the weight loss-associated improvements of traditional and non-traditional risk factors and the reduced long-term morbidity and mortality after bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 40 publications
4
39
0
3
Order By: Relevance
“…These findings highlight the possibility that improved post-operative neurocognitive outcomes may be a result of the effects of bariatric surgery on unique pathophysiological mechanisms associated with obesity. For instance, bariatric surgery has been shown to alter insulin resistance, circulating biomarkers (e.g., leptin, brain derived neurotrophic factor) and endothelial function [33-36]—all factors that have been linked with cognitive function. Other work suggests amyloid beta and inflammatory processes may play a key role [31].…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the possibility that improved post-operative neurocognitive outcomes may be a result of the effects of bariatric surgery on unique pathophysiological mechanisms associated with obesity. For instance, bariatric surgery has been shown to alter insulin resistance, circulating biomarkers (e.g., leptin, brain derived neurotrophic factor) and endothelial function [33-36]—all factors that have been linked with cognitive function. Other work suggests amyloid beta and inflammatory processes may play a key role [31].…”
Section: Discussionmentioning
confidence: 99%
“…An increased IMT, which indicates the pattern of initial structural lesions in the carotid arteries, has been reported in asymptomatic young overweight/obese subjects with metabolic syndrome 3) . Furthermore, an improved endothelial function and reduced IMT have been documented after bariatric surgery 18) , although the improvement in FMD is not always correlated with a reduction in weight and BMI 19) . Obesity-related vascular impairment occurs starting early in life; in autoptic reports of adolescents and young adults, obesity is associated with the extent When we divided the same group according to the median BMI values, we observed that the subjects with a higher BMI, although they had higher visceral fat area and HOMA-IR values, exhibited no significant differences in lipid parameters, FMD or IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, oxydized low density lipoprotein (LDL), intracellular adhesion molecule-1 (ICAM1), endothelin -1, eselectin, vascular endothelial growth factor-A (VEGF-A) and leptin (a possible mediator of left ventricolar hypertrophy) [47][48][49][50][51][52] . There is also reduction of inflammatory indexes such as erythrocyte sedimentation rate, which is known to predict coronary mortality 53 , as well as increase of adipokines, in particular adiponectin, which are associated with improved insulin sensitivity 54 , and reduction of high-sensitivity C-reactive protein 32 55 . Recently it has been also reported that HDL-cholesterol and its apoprotein ApoA4 significantly increase after gastric bypass surgery and that this increase is associated with net improvement in hepatic insulin sensititivity 56 .…”
Section: How Bariatric Surgery Prevents CV Diseasementioning
confidence: 99%
“…al also reported a significant improvement and in some patients, resolution of the histologic features of non-alcoholic fatty liver disease (NAFLD) together with reduction of plasma aminotransferase concentrations in LGB treated patients 64 . Finally, bariatric surgery has been reported to improve kidney function in both diabetic and non-diabetic subjects, the decrease of albuminuria being proportional to weight loss 65,66 .Even though logical and expected, many of the above mechanisms of action of bariatric surgery have been described in uncontrolled studies47,49,53,54,55,64,65 , thus making impossible…”
mentioning
confidence: 99%